Groundwater quality in coal mines of Ukraine: possibility of using it as drinking water - Shvets, I.; Zbykovskyy, Y.; Bohomaz, О. P.; Богомаз, О. П. (Polish Society of Ecological Engineering, 2025)
The article outlines the results of a study of groundwater in the mines of the Donetsk and Lviv-Volyn coal basins of Ukraine. Comparative analysis of groundwater in 9 mines of the Lviv-Volyn coal basin and 7 mines of the Donetsk coal basin confirmed the influence of the depth of mine workings on the quality of groundwater. It was established that there is a significant excess of standard values for water quality parameters: Hardness, content of chlorides, sulfates, calcium and magnesium. The use of groundwater from the “Centralna” mine is connected with the catastrophic deterioration of the situation with water supply to the population of Myrnohrad and Pokrovsk (Donetsk region) due to military actions. The study of groundwater in the “Centralna” mine was conducted using 122 parameters in the Chemical and Veterinary Inspection Offices of Stuttgart, Freiburg and Sigmaringen, Germany. Significant excesses of standard values were found for the following indicators: electrical conductivity, coloration, content of sulfate, sodium and chloride. The content of Trifluoroacetic acid was detected in groundwater, reaching 0.1360 μg/l. Analysis of groundwater after its preliminary treatment revealed no improvement in quality parameters. After treatment, the mine water contained Trifluoroacetic acid and Acesulfam-K E950. Their sources have not been identified.
Keywords: mine water; groundwater; chemicals; water quality standards; safety